Expression and diagnostic value of PIWI-interacting RNA by serum in acute myocardial infarction - Huang, Ying; Li, Yuan; Zhang, Kaiyu; Xu, Jingyi; Li, Ping; Yan, Xinxin; Sun, Kangyun (Journal of cardiology, 2023)
To detect the expression level of PIWI-interacting RNA in the serum of patients with acute myocardial infarction, and to explore the role of PIWI-interacting RNA in acute myocardial infarction. RNA was extracted from the serum of acute myocardial infarction patients and healthy subjects, and high-throughput sequencing of PIWI-interacting RNAs was performed to screen differentially expressed PIWI-interacting RNAs. Quantitative polymerase chain reaction was used to detect the expression of four differentially expressed PIWI-interacting RNAs in 52 patients with acute myocardial infarction and 30 healthy people. Receiver operating characteristic (ROC) curve was further used to analyze the correlation between differentially expressed PIWI-interacting RNAs and the occurrence of acute myocardial infarction. Kyoto Encyclopedia of Genes and Genomes analysis was used to analyze the role of PIWI-interacting RNA in the occurrence of acute myocardial infarction. RNA sequencing and bioinformatics analysis revealed that most piRNAs were upregulated in AMI patients, with 195 upregulated and 13 downregulated. Among them, piR-hsa-9010, piR-hsa-28646, and piR-hsa-23619 were significantly up-regulated in the serum of patients with acute myocardial infarction, but their expression in the acute heart failure group and coronary heart disease group was not significantly different from that in the healthy group. ROC curve analysis showed that piR-hsa-9010, piR-hsa-28646, and piR-hsa-23619 had high diagnostic values in acute myocardial infarction. In vitro, there was no significant difference in the expression of piR-hsa-9010 among THP-1, HUVEC, and AC16, while the expression of piR-hsa-28646 and piR-hsa-23619 in HUVEC was significantly higher than that in THP-1 and AC16. Pathway analysis showed that piR-hsa-23619 was mainly involved in TNF signaling pathway, and piR-hsa-28646 was mainly involved in Wnt signaling pathway. piR-hsa-9010, piR-hsa-28646, and piR-hsa-23619 were significantly up-regulated in the serum of patients with acute myocardial infarction. It can be used as a new biomarker for the diagnosis of acute myocardial infarction, which may be a therapeutic target for acute myocardial infarction. [Display omitted] •First study of piRNA expression in serum from acute myocardial infarction patients•Abundant and altered expression of piRNAs in acute myocardial infarction•PiRNAs may be used as biomarkers for the diagnosis of acute myocardial infarction.